Exploring the Correlation between Conceptual Understanding and Creativity Using Google Sites in Physics Learning - Johdi, Haerul; Gunawan, Gunawan; Ayub, Syahrial; Kosim, Kosim (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2024)
This study is one of the first to explore the potential of Google Sites as an interactive medium to simultaneously enhance conceptual understanding and creativity in physics education. The research aimed to determine the relationship between conceptual understanding and students' creativity. This study was conducted at SMA Negeri 1 Narmada with the research subjects being students of class XI MIPA 5. Data were collected using a test instrument. The correlation test analysis was conducted based on the results of the students' pretest and posttest. The results showed that the average pretest and posttest of students were obtained respectively of 39.80 and 84.71 for conceptual understanding and 36.76 and 80.91 for creativity. The analysis revealed a significant positive correlation between conceptual understanding and students' creativity, with a sig. (2-tailed) value of <0.001. The correlation coefficient was 0.567 for the pretest, indicating a moderate strength of relationship, and 0.787 for the posttest, suggesting a strong relationship. These findings suggest that integrating Google Sites into physics learning can effectively foster both conceptual understanding and creativity, potentially offering a scalable solution for improving critical educational outcomes.